Awareness among diabetic patient on ocular complication / Nurul Hanani Nanip - Nanip, Nurul Hanani (Faculty of Health Sciences, 2015)
Purpose: Diabetes mellitus is a significant cause of visual impairment, hence adequate knowledge on this condition and its ocular complications is of immense importance to diabetic patients. It affects virtually all ocular structures and can lead to blindness. This study was conducted to find out the knowledge and awareness of ocular complications among diabetic patients within Selangor. Methods: Sixty-three subjects were enrolled in this study. After signing the consent form, each of the subjects completed the questionnaires. The first set of questionnaire was set to obtained demographic data and inclusion criteria for the subject. The second set was set to investigate the awareness and knowledge of ocular complication among diabetic patients. Results: Majority of subjects were between 41 years to 50 years of age. Of forty-nine (77.8%) who were aware that eyesight function can be impaired by diabetes, more than half (68.3%) did not know the part of the eye that can be affected. Patient who have been diabetic below 10 years are more aware that diabetes can affect the eye than those with diabetic 10 years and above (63.7% vs 36.3% p = 0.001). Awareness of diabetic complications is better in those with tertiary education than others. Conclusion: We conclude that those who have been diabetic for 5-10 years are more aware of ocular complications of diabetes mellitus. This might be due to the sources of knowledge that can be easily accessed through reading in the internet and magazine. However, although the awareness of ocular complication is high, the level of knowledge is low. Health practitioners especially optometrist need to intensify health education through media, regular health talks in clinics to increase knowledge and increase health seeking behaviours of diabetics.